Penerapan Sistem Manajemen K3 Pada Pekerja Proyek Konstruksi Hotel Park Regis by Prince Menteng - Gita Lestari, Mayang; Irika Widiasanti; Arief Saefudin (Action Research Literate, 2023)
Occupational Health and Safety Management System (SMK3) is a protection system for labor and construction services to minimize and avoid the risk of moral and material losses, loss of working hours, as well as human safety and the surrounding environment which can later support effective and efficient performance improvement. Guidelines for the implementation of SMK3 in Indonesia are regulated in the Regulation of the Minister of Manpower Number: PER.05 / MEN / 1996. This research is to evaluate the application of the Occupational Health and Safety Management System in the Park Regis By Prince Menteng Hotel construction project during the project construction period. Based on the results and discussion, the application of the Occupational Health and Safety Management System (SMK3) to construction workers on construction work productivity of the Park Regis by Prince Menteng Hotel Project, it can be concluded that Occupational Health and Safety (K3) has a major influence on the productivity of Park Regis by Prince Menteng Hotel Construction Project workers. The implementation of Occupational Health and Safety (K3) in the Park Regis by Prince Menteng Hotel Project is still generally not good. This can be seen from the lack of discipline of workers who do not want to use personal protective equipment (PPE), reports of work accidents from finishing workers who are not careful so that workers' feet are hit by 6inch pipes, and the issuance of occupational safety and health warning letters as a warning to finishing workers who do not install cross base parts on scaffolding so that it can cause work accidents. The implementation of the occupational health and safety management system in the construction project of the Park Regis by Prince Menteng Hotel Construction must be immediately improved by focusing on workers who do not want to use personal protective equipment (PPE) with sanctions for workers.